2018
DOI: 10.1111/srt.12460
|View full text |Cite
|
Sign up to set email alerts
|

Handheld reflectance confocal microscopy, dermatoscopy and histopathological correlation of common inflammatory balanitis

Abstract: The use of handheld RCM as complementary tool in everyday clinical practice for the evaluation of inflammatory diseases involving sensitive areas such as male genitalia, may contribute to reduce the need of invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…Regarding dermoscopic appearance of Zoon plasma cell balanitis, our findings are in line with those coming from previous smaller studies, with orange structureless areas (diffuse or focal) and focused linear curved vessels being the most common features (over than 90% of cases) as well as the stronger parameters to differentiate this type of balanitis from EQ and psoriatic/candidal balanitis. From a dermoscopic–pathologic point of view, orange structureless areas and linear curved vessels respectively correspond to hemosiderin deposition and vascular dilatation in the dermis .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding dermoscopic appearance of Zoon plasma cell balanitis, our findings are in line with those coming from previous smaller studies, with orange structureless areas (diffuse or focal) and focused linear curved vessels being the most common features (over than 90% of cases) as well as the stronger parameters to differentiate this type of balanitis from EQ and psoriatic/candidal balanitis. From a dermoscopic–pathologic point of view, orange structureless areas and linear curved vessels respectively correspond to hemosiderin deposition and vascular dilatation in the dermis .…”
Section: Discussionsupporting
confidence: 91%
“…They were observed at a frequency ranging from 97.1% (135/139) to 100% (100/100, 83/83, 20/20). Red dots/globules were observed in lesions located on the trunk, extremities and the scalp, as well as on the face, genitals, palms, soles and skin folds …”
Section: Resultsmentioning
confidence: 99%
“…Red dots/globules were observed in lesions located on the trunk, extremities and the scalp, as well as on the face, genitals, palms, soles and skin folds. 4,8 The study of V azquez-L opez et al 7 revealed the coexistence of red lines and red dots in psoriatic plaques in an examination with a handheld dermoscope. According to authors, the presence of red lines may suggest the overuse of topical glucocorticosteroids.…”
Section: Dermoscopy Of Psoriatic Lesions Of the Skinmentioning
confidence: 99%
“…On dermoscopy, homogeneously distributed, dilated, and dotted vessels on an erythematous background are seen. [36]…”
Section: Inflammatory Disordersmentioning
confidence: 99%
“…On dermatoscopy, white structures which also appear pinkish are seen, which correspond to sclerosis on histopathology. [36] Gray-blue dots are arranged in peppering pattern, which corresponds to the dermal melanophages. Marked decrease in the concentration of vessels and presence of polymorphic patterns of vessels are the hallmark features [Figure 9b].…”
Section: Inflammatory Disordersmentioning
confidence: 99%